2012
DOI: 10.5578/tt.4634
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of inhaler technique and patient satisfaction with fixed-combination budesonide/formoterol dry-powder inhaler in chronic obstructive pulmonary disease (COPD): data on real-life clinical practice in Turkey

Abstract: Kronik obstrüktif akciğer hastalığında (KOAH) budesonid/formoterol sabit kombinasyon kuru toz inhaler için kullanım tekniğinin ve hasta memnuniyetinin değerlendirilmesi: Türkiye'de günlük klinik uygulama verileri Giriş: Bu çalışma, kronik obstrüktif akciğer hastalığında (KOAH) sıklıkla kullanılan kuru toz inhalerlere özgü hasta uyumunun düzeyini değerlendirmek ve seçilmiş bir inhaler tipi olarak budesonid/formoterol sabit kombinasyon kuru toz inhaler için hasta memnuniyetinin ve inhaler kullanım tekniğinin, Tü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 13 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…The multicentre character minimized the potential selection bias and allowed a better geographical representativeness. The FSI-10 questionnaire has been previously validated for Asthma and COPD [24,25], though it does not account for the determination of a minimally important difference [13]. Still, the results herein obtained have shown that both inhalers were well accepted by the patients, the mean score of all FSI-10 items was ≥4.0, with at least statistical significant differences favouring Breezhaler ® (a difference of 1.6 out of 50 points between devices).…”
Section: Discussionmentioning
confidence: 70%
“…The multicentre character minimized the potential selection bias and allowed a better geographical representativeness. The FSI-10 questionnaire has been previously validated for Asthma and COPD [24,25], though it does not account for the determination of a minimally important difference [13]. Still, the results herein obtained have shown that both inhalers were well accepted by the patients, the mean score of all FSI-10 items was ≥4.0, with at least statistical significant differences favouring Breezhaler ® (a difference of 1.6 out of 50 points between devices).…”
Section: Discussionmentioning
confidence: 70%
“… 9 However, there are inconsistent results with regard to whether age is related to the incorrect use of inhalers. 9 , 19 , 20 Öztürk et al 20 demonstrated that handling errors were especially common in the older group (≥65 years). The mean age of the patients enrolled in the current study was 72.10±8.98 years, and age was not associated with incorrect inhaler techniques ( Tables 2 and 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Education level was described to impact inhaler technique, although this remains a subject of debate [10]. A low educational level was shown to negatively impact the use of an inhaler in several studies [64,67,68,[72][73][74][75][76], but was not confirmed in others [77][78][79][80]. Interestingly, Pun et al [81] found a correlation between the educational level and the correct use of the Rotahaler ® DPI, but this correlation was not found for a pMDI.…”
Section: Education Levelmentioning
confidence: 99%